Molecular modelling and crystallographic investigation of novel synthetic cathinone 2-methyl-4'-(methylthio)-2-morpholinopropiophenone (MMMP) - Slabbert, Cara (University of Pretoria, 2024)
Dissertation (MSc (Chemistry))--University of Pretoria, 2024.